Recovery Of Valuable Iron Ore Concentrate Particles From The Process Rejects Of The Iron Ore Processing Plant Of Dalli Mines Of Sail, India - S. K. Pan (International Mineral Processing Congress, 2012)
The process flow-sheet adopted in treating hematite iron ore in India through wet circuit generates not only 15-25% slime of Run-of-Mine (ROM), but also results in loss of very high quality fine iron ore particles along with it. As the reserves of hematite iron ore is depleting, it is necessary to explore the possibility of upgrading other types of low grade iron ore and slime for recovery of iron minerals; extensive research in this field is being carried out. While beneficiation of low grade ore is yet to be established, slime beneficiation has been quite successful and many installations of slime treatment plant are underway. In SAIL mines, the slime is mainly the discarded particles from Classifiers, which are less than 0.2 mm sizes. R& D initiative has been focussed on the beneficiation of the slimes (49-60% Fe, 3-10% Al2O3 & 4-10% SiO2) of Dalli mines to generate concentrates assaying 62-64% Fe, 2-3% Al2O3, 3-4% SiO2 and a few innovative facilities for the same has been introduced at this mines of Bhilai Steel Plant (BSP). At Dalli mines, the slime is of very poor quality. A typical slime analysis assays 48.54% Fe, 15.1% SiO2, 8.5% Al2O3 and consists nearly 60% (by wt.) particles less than 38 micron. Slime analysis revealed substantial quantity of very high density mineral particles, those causes jamming of Thickener due to faster settling. A novel technique has been implemented to classify the concentrate ore particles from the gangue mineral particles by processing through Fluidized Bed Classifier (FBC) system, which is a gravity concentrator, to treat 50% of the slime generated and the rest is treated through de-sliming hydro-cyclone followed by Medium Intensity Magnetic Separator (MIMS). A special self-vibrating launder has been designed and introduced into the system to recover tiny iron ore particles, which could not get captured by the permanent Neodymium rare earth magnet in MIMS. The classified iron mineral particles from FBC are further treated in a battery of hydro-cyclones followed by modified Slow Speed Spiral Classifier (SSSC) unit. Multiple feed entry system to the SSSC unit is unique and use of particular feed entry point depends on the desired quality of the product and thus converted to a beneficiation equipment rather than mere de-watering unit. By processing slime in FBC system, the valuable iron ore particles with 62.5% Fe, 5.2% SiO2, 2.23% Al2O3 has been recovered from the slime at a material yield of 30%. And very high valued concentrate particles with more than 65% Fe has been sorted out through the magnetic separation route. The overall extra production of beneficiated slime concentrate is 40-45 tph with 63-64% Fe from a slime feed of 120-130 tph solid. This paper outlines few new approaches in iron ore slime beneficiation at Dalli mines for maximum recovery of valuable minerals. Keywords: fluidized bed classifier (fbc), iron ore slime of dalli mines, medium intensity magnetic separator, slow speed spiral classifier (sssc)